Levels of childhood vaccination coverage and the impact of maternal HIV status on child vaccination status in rural KwaZulu-Natal, South Africa - Ndirangu, James; Bärnighausen, Till; Tanser, Frank; Newell, Marie-Louise (Tropical medicine & international health, 2009)
Objectives  To analyse coverage of childhood vaccinations in a rural South African population and investigate whether maternal HIV status is associated with children’s vaccination status. Methods  2 431 children with complete information, 12-23 months of age at some point during the period January 2005 through December 2006 and resident in the Africa Centre Demographic Surveillance Area at the time of their birth were investigated. We examined the relationship between maternal HIV status and child vaccination status for five vaccinations [Bacillus Calmette-Guérin (BCG), diphtheria-tetanus-pertussis (DTP3), poliomyelitis (polio3), hepatitis B (HepB3), and measles] in multiple logistic regressions, controlling for household wealth, maternal age, maternal education and distances to roads, fixed and mobile clinics. Results  Coverage of the five vaccinations ranged from 89.3% (95% CI 81.7-93.9) for BCG to 77.3% (67.1-83.6) for measles. Multivariably, maternal HIV-positive status was significantly associated with lower adjusted odds ratios (AOR) of child vaccination for all vaccines [(AOR) 0.60-0.74, all P ≤ 0.036] except measles (0.75, P = 0.073), distance to mobile clinic was negatively associated with vaccination status (all P ≤ 0.029), household wealth was positively (all P ≤ 0.013) and distance to nearest road negatively (all P ≤ 0.004) associated with vaccination status. Conclusion  Positive maternal HIV status independently reduces children’s probability to receive child vaccinations, which likely contributes to the morbidity and mortality differential between children of HIV-positive and HIV-negative mothers. As a means of increasing vaccination coverage, policy makers should consider increasing the number of mobile clinics in this and similar communities in rural Africa.